Dual‐Mechanism Quenched Fluorogenic Probe Provides Selective and Rapid Detection of Cathepsin L Activity. (15th January 2021) - Schleyer, Kelton A.; Fetrow, Ben; Zannes Fatland, Peter; Liu, Jun; Chaaban, Maya; Ma, Biwu; Cui, Lina
Abstract: Cathepsin L (CTL) is a cysteine protease demonstrating upregulated activity in many disease states. Overlapping substrate specificity makes selective detection of CTL activity difficult to parse from that of its close homologue CTV and the ubiquitous CTB. Current probes of CTL activity have limited applications due to either poor contrast or extra assay steps required to achieve selectivity. We have developed a fluorogenic probe, CTLAP, that displays good selectivity for CTL over CTB and CTV while exhibiting low background fluorescence attributed to dual quenching mechanisms. CTLAP achieves optimum CTL selectivity in the first 10 min of incubation, thus suggesting that it is amenable for rapid detection of CTL, even in the presence of competing cathepsins. Abstract : Superior contrast : A novel c at hepsin L a ctivable p robe (CTLAP) has a chemical structure that provides high selectivity for its target while quenching its own background emission, resulting in superior contrast within 10 min of incubation and 120‐fold turn‐on fluorescence upon consumption. Thus, CTLAP reveals that chemical structure can influence photophysical properties as well as the selectivity of detection tools.